Molecular Structure, NMR, HOMO, LUMO, and Vibrational Analysis of O-Anisic Acid and Anisic Acid Based on DFT Calculations. (30th September 2013) - Mathammal, R.; Jayamani, N.; Geetha, N.
Abstract : This work deals with the vibrational spectroscopy of O-Anisic acid (OAA) and Anisic acid (AA). The fundamental vibrational frequencies and intensity of vibrational bands were evaluated using density functional theory (DFT) with standard B3LYP/6-31G** method and basis set combinations. The vibrational spectra were interpreted, with the aid of normal coordinate analysis based on a scaled quantum mechanical force field. The infrared and Raman spectra were also predicted from the calculated intensities. The effects of carbonyl and methyl substitutions on the structure and vibrational frequencies have been investigated. Comparison of simulated spectra with the experimental spectra provides important information about the ability of the computational method to describe the vibrational modes. The 13 C and 1 H NMR chemical shifts of the DFA and CA molecules were calculated using the gauge-invariant-atomic orbital (GIAO) method in DMSO solution using IEF-PCM model and compared with experimental data.